2018
DOI: 10.1002/mnfr.201800185
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of the Spinach Food Matrix on Lutein Bioaccessibility and Intestinal Uptake Lead to Unchanged Bioavailability Compared to Pure Lutein

Abstract: Opposite effects at the micellarization and intestinal cell uptake steps explain the lack of effect of spinach matrix on lutein bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The third part of this study aimed at assessing whether plant matrices, which contain physical barriers that can impair carotenoid diffusion, and which also contain carotenoids that can be in different physical states and that can be associated with different matrix molecules, can significantly affect the transfer efficiency. To that aim we chose two vegetables that are usual dietary sources of carotenoids, i.e., tomato and spinach, and we turned them into puree to mimic the size of their particles in the stomach during digestion. After having studied the transfer of carotenoids in the same conditions than those used for the pure carotenoids, we first observed that the transfer efficiency of the carotenoids incorporated in these matrices to the uncoated TG droplets was markedly lower than that of the pure carotenoids (supporting information Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third part of this study aimed at assessing whether plant matrices, which contain physical barriers that can impair carotenoid diffusion, and which also contain carotenoids that can be in different physical states and that can be associated with different matrix molecules, can significantly affect the transfer efficiency. To that aim we chose two vegetables that are usual dietary sources of carotenoids, i.e., tomato and spinach, and we turned them into puree to mimic the size of their particles in the stomach during digestion. After having studied the transfer of carotenoids in the same conditions than those used for the pure carotenoids, we first observed that the transfer efficiency of the carotenoids incorporated in these matrices to the uncoated TG droplets was markedly lower than that of the pure carotenoids (supporting information Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Canned spinach leaves were bought from a local supermarket (Casino brand). Canned spinach leaves were chosen in order to compare data obtained in this study with data obtained with the same spinach matrix in a previous study on the effect of spinach matrix on LUT bioaccessibility and bioavailability . To have a homogeneous matrix, spinach leaves were diluted four times with deionized water, i.e., 100 g drained spinach leaves were dispersed in a total volume of 400 mL water, and transformed in puree using a rotor stator homogenizer Silentcrusher (Heidolph, Grosseron, France) set at 16 000 rpm for 2 min under dim light at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with a recent study in minipigs aiming at comparing lutein response after pure lutein (i.e., without matrix) or spinach lutein ingestion. This study showed no difference in lutein responses, but the lutein peak was delayed from 2 to 6 h with spinach, [ 49 ] indicating that the food matrix can modulate micronutrient absorption rate.…”
Section: Discussionmentioning
confidence: 94%
“…Studies into the bacteria Propionibacterium freudenreichii , which is commonly used in production of fermented dairy products, showed that, in the growth period of P. freudenreichii , menaquinones were accumulated inside the cells, but, when the bacteria cells started lysing after depletion of lactose, the menaquinones was released from the cells [ 37 ]. It could be that, in Danablu 8 M, more cells have lysed and released the content of menaquinones, making them more bioaccessible.…”
Section: Resultsmentioning
confidence: 99%